Motor skills of soccer players aged 16-18 in regard to competition level and playing position - Momcilovic, Z.; Markovic, S.; Bogavac, D.; Milosavljevic Dukic, D.; Bugarski, S. (Facta Universitatis: Series Physical Education and Sport, 2020)
The aim of this paper was to examine the differences in the motor skills of soccer players aged 16-18 years who play in different competition levels (National League and Regional League), as well as players who play in different positions in the team. The standard testing battery for the motor skills assessment of soccer players was used to evaluate the motor skills. As for the evaluation of the differences between the different playing positions, a two-factor ANOVA with the factor Competition Level (National and Regional Level) and the factor Position (forward, midfielder, side defender, central defender) was used. A two-factor ANOVA with the factor Competition Level (National and Regional Level) and the factor Age (16, 17 and 18 years of age) was used to evaluate the differences between the different quality levels. The study included 126 male soccer players 16 to 18 years of age (N16=45, N17=41, N18=40) divided into 4 positions on the team: forwards (N=37, BH=179.2±5.0, BM=70.1±6.6), midfielders (N=48, BH=177.9±6.3, BM=69.6±7.9), side defenders (N=22, BH=176.6±5.4, BM=67.5±5.7) and central defenders (N=19, BH=184.0±4.3, BM=72.3±6.6). Because of significantly different activities in the field, the goalkeeper position was excluded from this study. The results indicate that motor skills do not differentiate players of different competition levels, and that there is a gap between players aged 18 years in aerobic endurance which is the basis of success in soccer. Also, the obtained results suggest that motor skills could differentiate players at certain positions. However, it was specifically found that only alactic capabilities type of speed and agility, differentiate forwards from other positions, especially from midfielders.